Methodological Approaches to Foreign Language Training of Future Specialists in the Context of Professional Activity - Dolynskiy, Ievgen (Pedagogical Discourse, 2025)
The article analyses the methodological foundations of foreign language training for future specialists in the context of their future professional activity. The study emphasises that modern higher education requires the integration of linguistic, professional, communicative, digital, and intercultural competences, which determine the content and structure of professionally oriented foreign-language training. The paper outlines the essence of key methodological approaches – competence-based, communicative, activity-based, personality-oriented, cultural, integrative, and technological – and clarifies their role in shaping effective educational strategies. Special attention is paid to the development of foreign-language professional competence through modelling real professional situations, the use of authentic materials, project-based learning, CLIL technology, and innovative digital tools that ensure interactive, practice-oriented learning. The research identifies current challenges in implementing methodological approaches in Ukrainian higher education, including heterogeneous levels of students’ foreign-language proficiency, insufficient readiness of teachers to apply CLIL and ICT-based methods, limited material resources, and the need to strengthen cooperation between universities and employers. The article highlights the importance of designing clear learning outcomes that correspond to the demands of the labour market, interdisciplinary integration, digitalization of educational processes, and the development of teachers’ methodological and communicative competences. It is argued that professionally oriented foreign-language training should be based on real communicative needs of future specialists, ensure continuous formation of autonomous learning skills, and stimulate students’ motivation through practical relevance of the tasks. The article proposes practical recommendations aimed at improving the effectiveness of foreign-language training: modernisation of curricula according to European standards, expansion of digital resources and blended learning, implementation of diagnostic assessment tools, creation of professional communicative training environments, and broader use of authentic professional discourse.